Parents and Teachers Collaboration in Children’s Education - Siti Rohimah; Suhadi Suhadi; Fachri Basalamah; Misbah Auliya (Edumaspul: Jurnal Pendidikan, 2024)
Collaboration between teachers and parents is considered important in educating children effectively. This research emphasizes the need for integrated roles and responsibilities between teachers and parents in educating children. Effective collaboration not only benefits a child's academic development, but also creates strong bonds between school and family, providing a solid foundation for a child's holistic growth and development. The research method used is a literature method with a focus on reviewing articles related to parent and teacher collaboration in children's education. Of the 28 articles studied, 17 articles were selected for in-depth analysis based on the criteria of relevance and full text availability. The research results show that active collaboration between parents and teachers, including two-way communication and participation in school activities, has a positive impact on children's development both at school and at home. Key findings highlight the importance of effective communication as the basis for the success of these collaborations, with a variety of communication methods, including technology, used to facilitate the exchange of information. Relationships built on trust and mutual understanding are the keys to successful collaboration. However, challenges such as unrealistic expectations or discipline problems also need to be handled carefully to focus on the child's interests.